Severe eosinophilia in a case of giardiasis - Rifat Nadeem Ahmad; Ahmed Sherjil; Asad Mahmood; Shahid Rafi (Mediterranean Journal of Hematology and Infectious Diseases)
A case of severe eosinophilia is reported in a child with giardiasis